ANALYSIS OF THE EFFECTIVENESS OF ZAKAT MAL DISTRIBUTION FOR HEALTH AND EDUCATION BY THE NATIONAL ZAKAT COMMUNITY AGENCY (BAZNAS) OF BOGOR REGENCY - Jamaluddin; Ujang Sumarwan; Qurroh Ayuniyyah; Sri Marti Pramudena (Referensi Islamika: Jurnal Studi Islam, 2026)
This study aims to analyze the effectiveness of zakat mal distribution in the health and education sectors by BAZNAS Bogor Regency in supporting the fulfillment of mustahik’s basic needs. This study employs a qualitative method with a descriptive approach. Data were collected through interviews, observations, and documentation involving six mustahik beneficiaries during the period of December 2023 to July 2024. Data analysis was conducted through data reduction, data display, and conclusion drawing. The findings indicate that the distribution of zakat in the health and education sectors has been relatively effective and in accordance with applicable regulations. The assistance provided has helped alleviate the burden of mustahik in meeting their basic needs. However, several challenges remain, including limited coverage of beneficiaries and the need to improve the equity of distribution. This study implies that the effectiveness of zakat distribution in the education and health sectors can serve as a basis for strengthening more targeted zakat distribution policies. The findings also highlight the important role of Zakat Collection Units (UPZ) in supporting the effectiveness of zakat distribution. Furthermore, the results may serve as a reference for developing more equitable and sustainable zakat distribution strategies. This study provides empirical contributions to the evaluation of zakat distribution effectiveness in the health and education sectors at the regional level. It also highlights the importance of enhancing distribution equity and targeting accuracy in zakat management to improve the sustainable welfare of mustahik.